Świat stworzony drogą do poznania Boga (Rz 1,19-20) - Ordon, Hubert (Verbum Vitae, 2017)
In the analyzed text, Rom 1:19-20, St. Paul states that people possess both the ability and the opportunity to know the true God, and they indeed actually achieve this knowledge. They acquire it thanks both to their own natural cognitive abilities and to the visible effects of God’s creative action in the natural world. This knowledge is not the product of a logical causal inference (i.e. from an effect back to its cause), but rather of intuition, which is an inner experience. It is rooted in reflection – but does not exclude reason – about the diversity of existing creatures, about the power of the forces of nature, the harmony perceptible in the natural realm, and the wisdom evident in the amazing design of the surrounding world.